2021
DOI: 10.1021/acs.analchem.0c04663
|View full text |Cite
|
Sign up to set email alerts
|

Fabric-Phase Sorptive Membrane Array As a Noninvasive In Vivo Sampling Device For Human Exposure To Different Compounds

Abstract: This study introduces an innovative device for the noninvasive sampling and chromatographic analysis of different compounds present in exhaled breath aerosol (EBA). The new sampling device, especially in light of the recent COVID-19 pandemic that forced many countries to impose mandatory facemasks, allows an easy monitoring of the subject’s exposure to different compounds they may come in contact with, actively or passively. The project combines the advantages of a fabric-phase sorptive membrane (FPSM) as an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Extraction/Dilution and LC-MS/MS Procedures. First, the chromatographic separation reported in another study 17 for the simultaneous analysis of more than 739 chemicals was tested. By applying the same chromatographic parameters, it was observed that the characteristics required, such as focusing the analytes in tight peaks to maximize the signal-to-noise ratio and consequently the sensitivity, avoiding the presence of matrix effects by resolving possible interferents through chromatography, and increasing the parameters for the correct identification considering also the reproducibility of the retention time, are maintained in the analyses of both liquid and solid seized samples.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Extraction/Dilution and LC-MS/MS Procedures. First, the chromatographic separation reported in another study 17 for the simultaneous analysis of more than 739 chemicals was tested. By applying the same chromatographic parameters, it was observed that the characteristics required, such as focusing the analytes in tight peaks to maximize the signal-to-noise ratio and consequently the sensitivity, avoiding the presence of matrix effects by resolving possible interferents through chromatography, and increasing the parameters for the correct identification considering also the reproducibility of the retention time, are maintained in the analyses of both liquid and solid seized samples.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…According to previous studies and some experiments [18,[21][22][23], it was agreed to use acetonitrile-potassium phosphate buffer (pH: 3.0) and its mixture (56:44, v/v) as the mobile phase. A C18 column [Waters XSELECT HSS C18 (100 x 4.6 mm, 3.5 µm), PN: 186004767 SN: 01113431413401] was used for analysis.…”
Section: Methods Optimizationmentioning
confidence: 99%
“…The feature of paper-in-facemask sampling is that adsorbed analytes can be directly analyzed for rapid screening. Locatelli et al [ 80 ] further developed a fabric-phase sorptive membrane (FPSM) array in facemask (FPSM array-in-facemask) to collect human exhaled breath metabolites for subsequently LC-MS analysis. The FPSM array-in-facemask showed that different sorbent coatings, including polar, nonpolar, and mixed mode, and zwitterionic phases, can be composed the powerful array to capturing a wide range of analytes regarding the metabolites and consumption of drinks, food, or drugs.…”
Section: Facemask Sapling Of Human Exhaled Aerosolsmentioning
confidence: 99%